Electrospun textiles from decellularized bovine pericardium and polyvinyl alcohol (PVA) supporting blood coagulation: innovative approach in biomaterials for research purposes - Di Nunno, Luca; Pagani, Veronica; Canciani, Elena; Ruocco, Gerardina; Spedicati, Mattia; Talmon, Maria; Fusaro, Luca; Di Francesco, Dalila; Casarella, Simona; Rizzi, Manuela; Boccafoschi, Francesca (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCurrent hemostatic agents face several limitations, including reduced effectiveness in controlling massive bleeding or preventing thrombogenic events. Functional bleeding control could allow time for further treatment and decrease mortality rates. Using suitable hemostatic agents may improve surgical outcomes by eliminating avoidable complications. Among all the patches available on the market, nanofibrous materials offer several advantages, among which the possibility to be properly designed in order to meet specific requirements related to bioactivity and biodegradability. Different patch formulations to support blood clotting are characterized in the present study.MethodsThe approach used is based on electrospun decellularized bovine pericardium (dECM) blended or layered with polyvinyl alcohol (PVA) and crosslinked by (3‐Glycidyloxypropyl)trimethoxysilane (GPTMS). Scanning electron microscopy and energy-dispersive X‐ray spectroscopy were used in order to characterize the scaffold’s morphology and chemical composition. Mechanical properties were evaluated using a tensile stress test, while wettability was measured using contact angle analysis. The electrospun textiles’ surface interaction with whole blood and platelet rich plasma (PRP) was also examined. Thromboelastography (TEG) and in vitro clotting assays were performed in order to evaluate the clot formation, while flow cytometry was used to verify platelet activation. Finally, in order to evaluate the biological response to the degradation by‐products of the electrospun textiles, cell viability was characterized through an indirect toxicity test using primary normal human dermal fibroblast (NHDF) as experimental model.Results and DiscussionOverall, the nanofibers-based textiles, optimized through blending and layering of dECM and PVA, successfully support stable clots. These biomaterials represent a valuable starting point for future research aimed to nanofibers’functionalization according to the desired application.